Urbanisation in India: Challenges, Opportunities and the Way Forward - Ahluwalia, !sher Judge; Kanbur, Ravi; Mohanty , P K; Mittal , A.K. (Gyan Management Journal, 2014)
Urban areas are integral to India's growth and development, accounting for around two-thirds of the country's GDP. Analysing India's rapidly expanding process of urbanisation, the book identifies the key challenges and opportunities and proposes suitable managerial and policy reforms. It addresses critical issues and puts forth suggestions for better planning financing alternatives and, most importantly, better governance for improved service delivery and affordable housing.THIS book focuses on the prescription-side of urban planning to tell us of what all is wrong with present-day urbanisation, the possible solutions and the way forward.Unfortunately, it makes little effort to unravel the knots on the implementation side that have kept similar prescriptions tied to the wall for all these years while our cities rot.
Keywords: development; GDP; urbanisation; importantly; prescription-side